Immunoglobulin G4-related masses surrounding coronary arteries: a case report. Issue 3 (8th March 2021) - Nakamura, Takuya; Goryo, Yutaka; Isojima, Takuya; Kawata, Hiroyuki
Abstract: Background: Immunoglobulin G4 (IgG4)-related disease (IgG4-RD) is an immune-mediated fibroinflammatory condition with high serum IgG4 levels affecting various organs, such as the pancreas, lacrimal and salivary glands, thyroid, kidney, and lung. Typical cardiovascular manifestations of IgG4-RD include periaortitis, coronary arteritis, and pericarditis. However, reports of IgG4-RD associated with coronary arteritis are rare. Here, we report a case of IgG4-related masses surrounding the coronary arteries. Case summary: A 59-year-old man was referred to our hospital because of mediastinal masses detected by computed tomography (CT). Coronary CT angiography revealed masses surrounding the right coronary artery and the left anterior descending coronary artery. An elevated serum level of IgG4 and histological findings led to the diagnosis of IgG4-related coronary arteritis with mass formation. Coronary angiography showed numerous feeding arteries to the masses, which were demonstrated as multiple microchannels in the intravascular ultrasound (IVUS) images. Discussion: IgG4-RD involving the cardiovascular system has been reported. However, coronary artery disease associated with IgG4-RD is very rare, and the mechanism of mass formation in IgG4-related coronary arteritis is unclear. In our case, within the cardiovascular system, IgG4-RD was limited to the coronary arteries, suggesting that the affected coronary arteries may provide the necessary blood supply to the mass, thus, aiding its growth. These findings were supported by the images from coronary angiography and IVUS.